Pemanfaatan Sampah Plastik dengan Metode Ecobrick Sebagai Upaya Mengurangi Limbah Sampah Plastik di Desa Cempaka Mulia Timur - Murni Murni; Norpita Sari; Selvi Noor Hidayah; Saufi Ramadhan (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
The implementation of this service program is intended so that the community can contribute to reducing environmental pollution as well as so that the community can also utilize plastic waste into valuable products. East Cempaka Mulia Village is a village located along the Cempaga River, the problem in this village is one of them related to plastic waste. This program aims to encourage residents to utilize waste that produces use value and also provide creative solutions in more sustainable waste management. The PAR (Participatory Action Research) method is a service approach that focuses on identifying problems in society and finding solutions to them (Problem Solving). The result of the service, namely overcoming plastic waste, is by recycling plastic waste using the ecobrick method, namely utilizing waste through plastic bottles.